Comparison of Coupled Flow-deformation and Drained Analyses for Road Embankments on CMC Improved Ground. (2016) - Mahdavi, Hamed; Fatahi, Behzad; Khabbaz, Hadi; Vincent, Philippe; Kelly, Richard
Abstract: The use of controlled modulus columns (CMC) is gaining increased popularity in the support of rail and road bridge approach embankments on soft soils. The further columns are driven into the competent firm soils, the further the design will rely on the inclusions to take the bulk of the vertical loads, as they become rigid inclusions. The advantage of this design approach is that it produces increased control over the settlement, but as a result the columns will attract greater loads, including bending moment and shear force in situations where non-uniform loading or ground conditions exist. The load on the composite soil-CMC is uniformly distributed by the upper layer of granular load transfer platform (LTP), which also includes a layer of reinforcement. Finite difference program FLAC3D has been used to numerically simulate an embankment on the improved ground with end-bearing CMC. A geosynthetic reinforcement layer has been simulated using the inbuilt FLAC 3D geogrid element. In this paper, a comparison has been made between the drained and coupled flow-deformation analyses. The force in the reinforcement layer, in particular, has been compared for the two analysis approaches. It was found that according to the numerical simulation, the drained analysis provides lower estimates of the settlement, lateral displacement; and therefore, predicts less tension in the geosynthetic layer.